Current Issues Of The Formation Of Future Schools Based On The Requirements Of The Times - Akhmedov I. N. (Euro Asian Journal Publishing, 2024)
This article covers current issues of the formation of future schools based on the requirements of the time, priorities for the implementation of educational policies in the school education system and issues of their organization, methodological recommendations and considerations on the requirements of today's teaching system.
Keywords: Deepening the reforms; carried out in the field of education; improving the system of training of pedagogical personnel